Elaborating ethnobotanical knowledge of bael (Aegle marmelos (L.) Corrêa) in augmented reality-based learning media with a STEM approach to increase students' naturalist intelligence - Rasyid, Abdur; Hardyanto, Wahyu; Ridlo, Saiful; Parmin, Parmin (Ethnobotany Research and Applications, 2024)
Background: Bael (Aegle marmelos (L.) Corrêa), a culturally and medicinally significant fruit in Asia, is increasingly unfamiliar to younger generations. This lack of ethnobotanical knowledge threatens its preservation. We propose an educational approach integrating science, technology, environment, and mathematics (STEM) with augmented reality (AR) to address younger generations' lack of ethnobotanical knowledge. Methods: This research employed a research and development (RnD) design involving ethnographic research and learning media development. Ethnographic research was conducted to assess respondents' ethnobotanical knowledge of bael, including general knowledge and misconceptions. The collected data informed the development of an AR-based learning media with a STEM approach using a 4D framework (defining, designing, developing, and disseminating). Results: The study revealed a low level of ethnobotanical knowledge among respondents, regardless of prior exposure to bael. A significant misconception was the confusion between bael and calabash. The developed AR-based learning media received positive feedback from validators and students. Large-scale trials demonstrated its effectiveness in significantly improving students' naturalistic intelligence scores. Conclusions: This research highlights the need to preserve ethnobotanical knowledge and offers an innovative solution through AR-based learning media with a STEM approach. The developed learning media can potentially enhance students' understanding of bael and other local plants, contributing to their naturalistic intelligence and promoting sustainable practices. Future iterations can be expanded to include more in-depth explanations of bael's uses and explore other local plant species. Keywords: STEM Education; Augmented Reality; Naturalistic Intelligence; Ethnobotanical knowledge; Bael fruit